ANALISIS RESEPSI KHALAYAK TERHADAP ISI PESAN IKLAN “DON’T KNOW KASIH NO” DALAM MEMAHAMI FENOMENA PHISING - Armansyah, Adhira Aurelia; Anam Miftakhul Huda (Universitas Negeri Surabaya, 2025)
Phishing is one of weak internet security as a service provider for ease and speed of information in the digital era. Cybercrime of phishing has occurred the banking industry in Indonesia since 2022. This study analyses the audience's reception of the advertisement